Societal Development in Rural China - Qian, Wenrong (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book provides a broad survey of Chinese rural households, examining ongoing changes in Chinese society and economy through the lens of the situation of rural families in China. Based on data from Zhejiang University's China Rural Household Panel Survey (CRHPS) in 2015 on rural households, which analyses all aspects of grass-roots rural households in China, this volume offers a scientific analysis of social development in rural China, exploring notably the basic structure, employment situation, income and expenditure, social security, and education situation of Chinese rural households, as well as the governance and public services of rural communities.